Electronic states in quantum rings: electric field and eccentricity effects - Lavenere-Wanderley, L. A.; Bruno-Alfonso, A.; Latge, A. (Iop Publishing Ltd, 2002)
The polarization effects of in-plane electric fields and eccentricity on electronic and optical properties of semiconductor quantum rings (QRs) are discussed within the effective-mass approximation. As eccentric rings may appropriately describe real (grown or fabricated) QRs, their energy spectrum is studied. The interplay between applied electric fields and eccentricity is analysed, and their polarization effects are found to compensate for appropriate values of eccentricity and field intensity. The importance of applied fields in tailoring the properties of different nanoscale materials and structures is stressed.